(untitled) (Research, Society and Development, 2021)
This article is the result of an experiment carried out to learn argumentative text. As active methodologies, although discussed for some time by progressive thinkers of education gained notoriety with the advancement of informatics. As denominations are diverse, but with one element in common: the student as protagonist in the learning process. Therefore, aiming the development of skills related to planning of autonomous production of gender, a discursive opinion article, using in flipped Classroom and in digital mind map. The intervention carried out is guided by action research, to validate the hypothesis that the application of active methodologies combined with digital technologies can contribute to the formation of critical thinking and student autonomy. It was concluded that the freedom of thematic choice and the systematization of the central elements of the argumentative text are relevant to a more meaningful and automatic production, differing from the applied practice in the teaching of argumentation.